Channel architecture via self assembly of oxamide oximes complexes - Yüksel, Fatma; Gumus, Gulay; Gurol, Ilke; Ahsen, Vefa; Chumakov, Yurii; Jeanneau, Erwann; Luneau, Dominique (Royal Soc Chemistry, 2008)
The nickel(II) and palladium( II) complexes of oxamide oximes substituted with alkyl chains of different length (C4-C8) were synthesized from the reaction of dichloroglyoxime with the corresponding amine derivatives. All compounds have been characterized by X-ray diffraction on single crystals and were found to be centrosymmetric at the metal center which is bound by the four oximic nitrogen atoms of two ligands in a square planar environment. Crystal structure analyses of Ni(II) and Pd(II) complexes showed that all of the Pd( II) complexes but only the hexyl-substituted oxamide oxime Ni( II) complex form infinite tubular channels. Their conformational analyses were carried out in order to understand the role of the chain length and of the metal center in the formation of the tubular channels and it was found that the formation of infinite tubular channels in crystals of Ni( II) and Pd( II) alkyl-substituted oxamide oxime complexes is related to the orientation of the alkyl chains relative to the central core.
Keywords: Supramolecular Architectures; Crystal-Structures; Frameworks; Adsorption; Chemistry; Network